JURIDICAL ANALYSIS OF PEOPLE OF THE CRIME OF PLANNING MURDER AS JUSTICE COLLABORATORS ACCORDING TO CRIMINAL LAW IN INDONESIA - Sinaga, Hasudungan (IBLAM LAW REVIEW, 2022)
The murder incident involving several police officers as the perpetrators of the victim who was also a member of the National Police made this case attract public attention. It was concluded that this case was a case of ordinary murder between fellow police officers using a shootout mode, but because one of the witnesses volunteered as a Justice Collaborator, this case was not an ordinary murder case, but rather a murder that had been planned and there was an attempt to manipulate the case involving dozens of police officers. Several police officers were even prosecuted because they were considered an obstruction of justice in this case. This research aims to see the position of the Justice Collaborator Provisions in the Criminal Law System in Indonesia and how the Justice Collaborator is implemented in Premeditated Murder Crime Cases based on the South Jakarta District Court Decision Case Study Number 798/Pid.B/2022/PN.Jkt.Sel. ). This type of research is normative legal research, using a statutory regulation approach, concept approach and case approach. The author concludes that the justice collaborator provisions in the legal system in Indonesia are that the perpetrator is not the main perpetrator and the case he experienced was a particular case that could cause serious disruption to society. Apart from that, perpetrators who are declared justice collaborators must be given awards for their cooperation in uncovering cases. Based on the judge's considerations and decisions, the perpetrator can be designated as a justice collaborator because he is not the main actor but only as an errand boy. As for the case, even though it is classified as a conventional crime, this case is considered to be undermining the image of the police institution because there was an attempt to fabricate the case by the intellectual actor who was a high-ranking National Police official.